Evaluation of Visunex Medical's PanoCamTM LT and PanoCamTM Pro wide-field imaging systems for the screening of ROP in newborn infants. (2nd August 2016) - Wood, Edward H.; Moshfeghi, Andrew A.; Nudleman, Eric D.; Moshfeghi, Darius M.
ABSTRACT: Introduction : Retinopathy of Prematurity (ROP) is a leading cause of childhood blindness. The incidence of ROP is rising, placing greater demands on the healthcare providers that serve these patients and their families. Telemedicine remote digital fundus imaging (TM-RDFI) plays a pivotal role in ROP management, and has allowed for the expansion of ROP care into previously underserved areas. Areas covered : A broad literature review through the pubmed index was undertaken with the goal of summarizing the current state of ROP and guidelines for its screening . Furthermore, all currently used telemedicine remote digital fundus imaging devices were analyzed both via the literature and the companies' websites/brochures. Finally, the PanoCam LT™ and PanoCam™ Pro created by Visunex Medical were analyzed via the company website/brochures. Expert commentary : The PanoCam LT™ and PanoCam™ Pro have recently been approved for use within the USA and CE marked for international commercialization in European Union and other countries requiring CE mark. These wide-field imaging systems have the intended use of ophthalmic imaging of all newborn babies and meet the requirements for ROP screening, thereby serving as competition within the ROP screening market previously dominated by one camera imaging system.